A review of response interruption and redirection: 2007–2021. (12th May 2022) - Ryan, Joseph; Rosales, Rocío; Rowe, Emily
Abstract: The objective of this paper is to provide a review of the current state of the literature on response interruption and intervention (RIRD) beginning with the year the term was first coined. The paper aims to replicate and refine previous reviews on this topic by including: (1) only articles that used the term "RIRD"; (2) all behaviorally oriented journals with publications on the topic; (3) articles that evaluated RIRD across multiple topographies of automatically reinforced behavior; and (4) an evaluation of measures of treatment integrity, social validity, maintenance, and generality. Suggestions for future research and use of RIRD in clinical practice will be discussed.